Organometallic derivatives of natural products: dicobalt hexacarbonyl complexes of geranyl-alkynes. (1st August 2016) - Moore, Angela; Ostermann, Johannes; Ortin, Yannick; McGlinchey, Michael J.
Abstract : Di- and tri-cobalt carbonyl clusters bearing geranyl or neryl substituents offer potential routes to novel terpenoid systems. Abstract : Treatment of methyl geranyl ether with diiron nonacarbonyl leads to hydrogen migration to form previously unknown E and Z 1-methoxy-3, 7-dimethyl-1, 6-octadiene in low yield. Sodium propargyl alkoxide and geranyl bromide yield propargyl geranyl ether, 13 ; subsequent reaction with dicobalt octacarbonyl and then bis(diphenylphosphino)methane furnishes the corresponding alkyne–Co2 (CO)4 (dppm) tetrahedral cluster, 16 . Reaction of geranylacetone with phenylethynyl-lithium, and then with Co2 (CO)8, forms (1-phenyl-3, 7, 11-trimethyldodeca-6, 10-dien-1-yn-3-ol)Co2 (CO)6, 19 . The carbynyltricobaltnonacarbonyl clusters RC(O)CCo3 (CO)9, where R = geranyl, 23, or farnesyl, 25, are preparable in very good yield either by reaction of the appropriate alcohol with trichloroacetyl chloride and then Co2 (CO)8, or by reaction with the metal-stabilized acylium ion [Co3 (CO)9 CCO] +, 24 . Potential use of these (η 2 -alkyne)dicobalt complexes in Pauson–Khand or Nicholas cyclizations is discussed.